Effect of Lactic Acid Bacteria and Propionic Acid on Fermentation Characteristics, Chemical Composition, and Aerobic Stability of High-Moisture Corn Grain Silage - Jinze Bao; Lei Wang; Zhu Yu (Microorganisms)
This investigation aimed to assess the effect of additives on the aerobic stability, fermentation profile, and chemical composition of high-moisture corn grain silage. The corn grain was milled and divided this into four distinct treatment groups: Lentilactobacillus buchneri, propionic acid, Lactiplantibacillus plantarum, and no additive (control). The capacity of the silos was 1 L and density was 1000 kg/m3. Each group had three replicates and was fermented for 45 d. At silo opening, one part of silage was used for fermentation parameters, chemical composition, and in vitro dry matter digestibility analysis; another part was used for aerobic stability determination. Compared with the control, all additives increased lactic acid and dry matter concentrations (p < 0.001) and decreased neutral detergent fiber level (p < 0.001). In comparison with the control, the application of Lentilactobacillus buchneri and propionic acid improved silage aerobic stability, showed by lower pH level and yeast and mold populations after exposure to air. The findings offer theoretical groundwork and technological backing for the use of high-moisture corn grain silage.